“Well, the Message Is From the Institute of Something”: Exploring Source Trust of Cancer-Related Messages on Simulated Facebook Posts - Trivedi, Neha; Krakow, Melinda; Hyatt Hawkins, Katherine; Peterson, Emily B.; Chou, Wen-Ying Sylvia (Frontiers in Communication, 2020)
Growing evidence points to the significant amount of health misinformation on social media platforms, requiring users to assess the believability of messages and trustworthiness of message sources. This mixed methods experimental study fills this gap in research by examining social media users’ (n=53) trust assessment in simulated cancer-related messages using eye-tracking, surveys, and cognitive interviews. Posts varied by information veracity (evidence-based vs. non-evidence-based) and source type (government agency, health organization, lay individual); topics included HPV vaccination and sun safety. Among sources, participants reported trusting the government more than individuals, regardless of veracity. When viewing non-evidence-based messages, participants reported higher trust in health organizations than individuals. Participants with high trust in message source tended to report high message believability. Furthermore, attention spent on viewing the source of the post was not associated with the amount of trust in the source of message, which suggests that participants may have utilized other cognitive heuristics when processing the posts. Through post-experiment interviews, participants described higher trust in government due to reputation and familiarity. Further verification of the quality of information is needed to combat the spread of misinformation on Facebook. Future research should consider messaging strategies that include sources that are already trusted and begin to build trust among other credible sources.